A promising ultrafast pulse laser crystal with a disordered structure: Yb3+:Sr3Gd2(BO3)4. Issue 12 (3rd March 2017) - Sun, Shijia; Wei, Qi; Lou, Fei; Huang, Yisheng; Yuan, Feifei; Zhang, Lizhen; Lin, Zhoubin
Abstract : The disordered structure, polarized spectral properties and laser performances of the Yb 3+ :Sr3 Gd2 (BO3 )4 crystal reveal its promising potential for generating ultrafast pulse lasers. Abstract : A Yb 3+ -doped Sr3 Gd2 (BO3 )4 (Yb:SGB) crystal was grown using the Czochralski method. A systematic investigation of the disordered structure characteristics, polarized spectral properties and continuous wave (CW) laser performances of this crystal was reported for the first time. Due to the statistical distributions of Gd 3+ and Sr 2+ ions, the absorption and emission spectra are strongly inhomogeneously broadened when introducing Yb 3+ in the host. This feature of the broad spectra facilitates efficient pumping of InGaAs diodes and production of ultrafast pulse lasers. A maximum CW laser output power of 2.82 W under an absorbed pump power of 6.4 W was achieved with a central wavelength of 1055 nm, corresponding to a slope efficiency of 54% and an optical conversion efficiency of 44%. The results reveal that Yb:SGB is an excellent candidate for an ultrafast pulse laser crystal.